Integrating rubber with sentang - current agroforestry practice / Ahmed Azhar Jaafar … [et al.] - Jaafar, Ahmed Azhar; Kasiran, Norman; Muhammed, Suhaimi; Wan Ismail, Wan Hanisah (2004)
In a research conducted to gather information about the agroforestry practices in Peninsular Malaysia, integration of plantation crop (rubber) and timber tree (sentang) was found to be the most common. type (27.3%). Smallholder farmers preferred sentang, a fast growing timber species to supplement the low income generated by rubber especially during the low productive periods and during replanting. Most farmers employed hedge planting system (70%) which can be either alternate rows or alternate strips. Sentang tends to grow faster in rubber plantations but has smaller trunk diameter than in oil palm plantations. Normal agricultural management practices were implemented as in monocropping but no adverse effects in relation to plant growth and yield to the plantation crop (rubber) was observed. This indicates that integration of rubber and sentang is a viable approach to improve farm income.